Radiocarbon Dating of the Nyixoi Chongco Rock Avalanche, Southern Tibet: Search for Signals of Seismic Shaking and Hydroclimatic Events - Ha, Guanghao; Liu, Feng; Cai, Maotang; Pei, Junling; Yao, Xin; Li, Lingjing (Frontiers in Earth Science, 2022)
Landslides are important agents of the surface processes involved in the growth of mountainous topography. Dating prehistoric landslides is a prerequisite for establishing the relationships between prehistoric slope instability, and past climatic regimes and paleoseismic records. The Nyixoi Chongco rock avalanche (NCRA) is located in the Angang graben within the N–S trending rift zone in southern Tibet. It represents a giant prehistoric mass wasting event that was characterized by exceptional mobility and a large volume. However, the exact emplacement time and origin of the NCRA are still controversial. In this study, we conducted 14C dating of peat layers and snail shells to constrain the emplacement age of the NCRA. The 14C ages of the organic material and plant remnants in the basal peat layer are 1272–1389 and 1299–1404 cal AD, respectively. The 14C ages of aquatic snail shells and the bog overlying the rock avalanche are 425–565 and 1022–159 cal AD, respectively. These results indicate that the NCRA consisted of at least two separate and distinct events, instead of the single event suggested by previous studies. Based on field investigations and temporal correlations, we infer that there may be no paleoseismic records in the Angang graben that would corroborate a coseismic trigger for the NCRA. Therefore, we suggest that the 14C ages of the sediments below and above the landslide rocks should be interpreted carefully. The 14C ages alone do not provide sufficient evidence to infer the true trigger of the NCRA event.